Model Arsitektur Backpropagation Dalam Meramalkan Jumlah Tindak Pidana Menurut Kepolisian Daerah Sumatera Utara - Annisa, Liza; Isnaini, Alvina; Windarto, Agus Perdana (Journal of Informatics, Electrical and Electronics Engineering, 2023)
A criminal act is a violation that can involve communities and is related to the law. The purpose of this study is to create the best architectural model using the backpropagation method where the best model can be used to predict the number of criminal acts according to the regional police in North Sumatra. The dataset used is sourced from the Central Statistics Agency of North Sumatra on the number of criminal acts in 2001-2020. The method used is the backpropagation method. The analysis process uses the help of Matlab 6.1 software. From the trials conducted using several architectural models 9-4-1, 9-8-1, 9-12-1, 9-16-1, and 9-20-1, the best architectural model is the 9-8 model. -1 with 90% correctness accuracy and MSE 0.0009992573.